Urinary incontinence rehabilitation of after radical prostatectomy: a systematic review and network meta-analysis - Yu, Kai; Bu, Fan; Jian, Tengteng; Liu, Zejun; Hu, Rui; Chen, Sunmeng; Lu, Ji (Frontiers in Oncology, 2024)
Purpose The aim of this study is to provide treatment for patients with urinary incontinence at different periods after radical prostatectomy. Methods The PubMed, Embase, Cochrane, and Web of Science were searched for all literature on the effectiveness on urinary control after radical prostate cancer between the date of database creation and 15 November 2023 and performed a quality assessment. A network meta-analysis was performed using RevMan 5.3 and Stata 17.0 software and evaluated using the surface under the cumulative ranking curve. Results The results of the network meta-analysis showed that pelvic floor muscle therapy including biofeedback with professional therapist–guided treatment demonstrated better results at 1 month to 6 months; electrical stimulation, biofeedback, and professional therapist guidance may be more effective at 3 months of treatment; professional therapist–guided recovery may be less effective at 6 months of treatment; and combined therapy demonstrated better results at 1 year of treatment. During the course of treatment, biofeedback with professional therapist–guided treatment may have significant therapeutic effects in the short term after surgery, but, in the long term, the combination of multiple treatments (pelvic floor muscle training+ routine care + biofeedback + professional therapist–guided treatment + electrical nerve stimulation therapy) may address cases of urinary incontinence that remain unrecovered long after surgery. Conclusion In general, all treatment methods improve the different stages of functional recovery of the pelvic floor muscles. However, in the long term, there are no significant differences between the treatments. Given the cost-effectiveness, pelvic floor muscle training + routine care + biofeedback + professional therapist–guided treatment + electrical nerve stimulation therapy within 3 months and pelvic floor muscle + routine care after 3 months may be a more economical option to treat urinary incontinence. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=331797, identifier CRD42022331797.